EFL Students’ Preferences of Artificial Intelligence (AI) for Writing - Safitri, Bujing; Dewi, Utami; Ramadhan, Achmad (CV. ITTC INDONESIA, 2024)
This study examines the preferences of EFL (English as a Foreign Language) students regarding the use of artificial intelligence (AI) in writing, specifically at the State Islamic University of North Sumatra. The study explores how AI tools such as DeepL Translator, Google Translator, Grammarly, QuillBot, and ChatGPT enhance students' writing quality. Data was collected through questionnaires and semi-structured interviews from 15 students in the English Education program. The results indicate that DeepL Translator is the preferred tool for translation due to its editing flexibility, followed by Google Translator and QuillBot. QuillBot and Grammarly dominate in grammar checking, chosen for their ability to boost students' confidence in writing. ChatGPT is the most commonly used AI for generating writing ideas, while QuillBot ranks highest for paraphrasing. These findings reveal that although AI provides quick and specific feedback, there are concerns about over-reliance on this technology. The study concludes that while AI is a practical writing aid, its use should be balanced to avoid hindering the development of independent writing skills. This research provides important insights into integrating AI in writing instruction in EFL environments.